2005
DOI: 10.1063/1.2126794
|View full text |Cite
|
Sign up to set email alerts
|

Discovering inch-diameter metallic glasses in three-dimensional composition space

Abstract: Articles you may be interested inCalculation of driving force and local order to predict the favored and optimized compositions for Mg-Cu-Ni metallic glass formation Abnormal behavior of supercooled liquid region in bulk-forming metallic glassesWe have discovered low-cost bulk metallic glasses ͑BMGs͒ with diameters as large as 16 to 25 mm based on the ordinary engineering metal Mg. We also use this example to present a new strategy, to illustrate how to navigate in three-dimensional composition space for locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
119
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(130 citation statements)
references
References 24 publications
2
119
0
1
Order By: Relevance
“…[1][2][3][4][5][6] The underlying mechanisms for the high glass forming ability (GFA) of these alloys are not completely understood. From a structural point of view, BMGs should have similar structures as their corresponding liquids.…”
Section: Qk Jiang Zy Chang Xd Wang and Jz Jiangmentioning
confidence: 99%
“…[1][2][3][4][5][6] The underlying mechanisms for the high glass forming ability (GFA) of these alloys are not completely understood. From a structural point of view, BMGs should have similar structures as their corresponding liquids.…”
Section: Qk Jiang Zy Chang Xd Wang and Jz Jiangmentioning
confidence: 99%
“…It has been found that microalloying with proper alloying elements can dramatically improve the GFA of various BMGs [23][24][25]. Previous studies showed that the GFA of Cu-, Mg-and ZrCu-based bulk metallic glasses were significantly enhanced by adding Ag [26][27][28][29]. In this work, Ag was also chosen as the doping element in the Zr 35 Ti 30 Cu 7.5 Be 27.5 system, which had a critical diameter of about 15 mm and a wide supercooled liquid region of 165.1 K [30].…”
mentioning
confidence: 99%
“…In the past decades, a number of BMGs with maximum diameter of at least 10 mm have been synthesized in many multi-component alloy systems. [1][2][3][4][5][6] Among the bulk glassforming alloys, Cu-based BMGs were recognized to be a promising structural materials due to relatively high strength, good ductility and low cost, and the maximum diameter is reported to be 10 mm for Cu 46 Zr 42 Al 7 Y 5 and Cu 44:25 Ag 14:75 -Zr 36 Ti 5 alloys. 2,7) It is well known that binary Cu 50 Zr 50 alloy has a good glass-forming ability (GFA).…”
Section: Introductionmentioning
confidence: 99%